Casos y cosas: semanario popular (Vol. 1, No. 38) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Juventud!, Reflexiones de un ocioso, Que se persigue?, Escandalos a granel, Al travéz de los Andes, Salvajismo policial, Por esos mundos.... Contrastes callejeros, Rectificando

ENGLISH: Youth, reflections of an idle man, who pursues himself, scandals galore, across the Andes, police savagery, for those worlds .... Street contrasts, rectifying
Cases and things: popular weekly (Vol. 1, No. 38)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas